Monofunctional and dendritic schiff base (N, N′) ruthenium carbene - Tancu, Yolanda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.